2020
DOI: 10.1155/2020/3526316
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Lamellar Macular Holes: A Review

Abstract: is literature review aims to provide the retina specialist with answers to patient's questions related to the management of lamellar macular holes (LMHs). Most LMHs are stable over time, but 13-21% present an anatomic decline after 18-24 months of follow-up. Nineteen point five percent of the eyes may experience a visual acuity (VA) loss of more than 5 letters after 3 years. Many surgeons choose to perform surgery when there is significant metamorphopsia or documented decline in VA over time. e typical surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…They obtained an AUROC curve of 0.75. Drusen regression has been shown to precede the progression of non-exudative AMD (49)(50)(51)(52).…”
Section: Deep Learning and Age-related Macular Degenerationmentioning
confidence: 99%
“…They obtained an AUROC curve of 0.75. Drusen regression has been shown to precede the progression of non-exudative AMD (49)(50)(51)(52).…”
Section: Deep Learning and Age-related Macular Degenerationmentioning
confidence: 99%
“…Thus, an earlier intervention that can stabilize the foveal configuration may be advantageous in certain cases. Nevertheless, most of the available studies have only shown a stabilization or possible moderate gain in visual acuity after vitrectomy with ILM peeling in progressive LMHs [10]. Recent publications report similar results with the so-called LHEP embedding technique, in which LHEP becomes embedded in the foveal defect during vitrectomy [13].…”
Section: Discussionmentioning
confidence: 94%
“…Such an acute event probably determined the patients to confront their apprehension about coming to a hospital during a lockdown period. Postoperative complications of cataract surgery are also suscepti-ble to be rapidly diagnosed and emergency therapy is of utmost importance (13,14,15,16,17,18). Special interdisciplinary procedures helped reduce the length of hospital stay (18).…”
Section: Discussionmentioning
confidence: 99%